The Application Of Raw Materials Controlling In UD Chandra Group - Islami, Beby Mutiara; Wibowo, Januar; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
UD Chandra Group is a manufacture company which focused in selling softcase. The brand which is developed is ultimate brand. The brand has already dotted throughout Indonesia such are Surabaya, Jember, Banyuwangi, Kediri, Malang, Madiun, Yogyakarta and other big cities. There two types of softcase, double type and single type which each size are 10 inch, 11.6 inch, 12 inch and 14 inch. Until now, in purchasing raw materials, the company refers to customer demand from the previous transaction and the waste stock in bond. Therefore, the company has not supplied the raw materials optimally yet. However, raw materials control application is needed to overcome the problem in supply the raw materials. Raw materials inventory control application provides some menu for calculate forecasting customer demand, including method such as Single Exponential Smoothing (SES) method, Double Exponential Smoothing (HOLT) method and Triple Exponential Smoothing (WINTER) method. That prediction methods are used to predict the customer demand in the future and provide the number of raw materials for the next period. The number result is used as the reference to process the calculation of reorder point (ROP). Reorder point is used to determine the raw materials reorder.